New insights in the mode of action of anti-leishmanial drugs by using chemical mutagenesis screens coupled to next-generation sequencing - Arijit Bhattacharya; Sophia Bigot; Prasad Kottayil Padmanabhan; Angana Mukherjee; Adriano Coelho; Philippe Leprohon; Barbara Papadopoulou; Marc Ouellette (Microbial Cell)
Leishmania parasites are responsible for a range of clinical manifestations ranging from self-resolving cutaneous sores to life-threatening diseases. The management of leishmaniasis is complicated in part by the scarcity of treatment options but also by the emerging or established resistance to available drugs. A major driver of resistance in Leishmania is the amplification of resistance genes taking advantage of the highly repetitive genomic landscape of the parasite. The recent advent of whole genome gain of function screens gave new momentum to the study of such resistance mechanisms, leading to the identification of novel resistance factors and drug targets against approved drugs, which include antimony (SbIII), miltefosine (MIL), paromomycin (PMM), and amphotericin B. However, these screens do not pinpoint single nucleotide variations (SNVs), an important contributor of drug resistance. To fill the gap, our recent study describes the optimization of chemical mutagenesis coupled to next generation sequencing, an approach called Mut-seq, as a way to explore networks of drug resistance genes in organisms with a diploid to mosaic aneuploid genome like Leishmania. Our Mut-seq screen revealed associations between genes linked with lipid metabolism and resistance to MIL, and highlighted the role of a protein kinase in translation leading to resistance to PMM.